Validação do questionário Childhood Asthma Control Test (c-ACT) para o Brasil - Oliveira, Suelen Goecks (2015)
Introduction: Children’s own perceptions and accounts of their asthma diagnosis have proved to be reliable and relevant to disease control. Objective: The aim is to validate the Brazilian Portuguese version of the Childhood Asthma Control Test (c-ACT) in children aged between 4 and 11 years. Methods: The investigation was divided into two stages: The first stage comprised the translation and linguistic adaptation of the instrument, while the second consisted of testing the psychometric properties of validity and reliability. Results: A total of 105 participants were included, aged between 4 and 11 years. Validity: all correlations between the total score and items on the questionnaire were significant and obtained values of r = > 0.3. There was no correlation between the total score of the questionnaire and lung function. The controlled asthma group showed significantly higher c-ACT scores than those of the uncontrolled asthma group (controlled 22±2.9 VS uncontrolled 16.3±5.3 p <0.001). Reliability: The Alfa de Cronbach coefficient for the total c-ACT score was 0.677 (CI95% 0.573-0763). In the assessment of sensitivity to change, the effect size was 0.8 and the intraclass correlation coefficient was 0.598. No floor or ceiling effects were observed in the sample studied. Completed: The Brazilian version of the Childhood Asthma Control Test proved to be valid and reliable.